Security and Resilience in the Software Development Life Cycle - Raghavan, Lakshmikanth; Merkow, Mark S (Secure and Resilient Software Development, 2010)
In Chapter 1 we introduced the need for resilient software and looked at the consequences of software failures and security breaches due to poorly written and sometimes poorly conceived software. In Chapter 2 we explored nonfunctional requirements that lead to high-quality and resilient software and began to understand their role in systems requirements gathering and analysis steps.